The role of negative automatic thoughts as a mediator in the relationship between maternal attachment and depressive symptoms among late adolescents of Pakistan - Irfan, Siddrah; Zulkefly, Nor Sheereen; Tan, Kit Aun; Ismail, Siti Irma Fadhilah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Negative automatic thoughts refer to subconscious thinking patterns in response to irrational and self-defeating stimuli. Individuals who are depressed tend to have biased negative automatic thoughts. Therefore, there is a need to refine our understanding of what contributes to the development of adolescent depressive symptoms. The current study examined the mediating role of negative automatic thoughts in the link between maternal attachment and depressive symptoms among late adolescents in Pakistan. Methods: This cross-sectional study focused on 936 (males=423, females=513) students aged 17 to 19 years old, who were selected through multistage cluster sampling technique. Respondents answered self-report questionnaires which assessed maternal attachment, depressive symptoms, and negative automatic thoughts. Structural equation modelling was utilised to analyse the relationships among the research variables. Results: The findings indicated that 39.3% had negative automatic thoughts; whereas, 5.6% experienced severe depressive symptoms. Correlational analysis showed that maternal attachment had a negative association with depressive symptoms and negative automatic thoughts. In contrast, depressive symptoms were positively related to negative automatic thoughts. Structural analysis revealed that negative automatic thoughts partially mediated the association of maternal attachment with depressive symptoms among late adolescents. Findings specifically demonstrated that those with insecure maternal attachment tend to have negative automatic thoughts, which subsequently lead to depressive symptoms. Conclusion: In conclusion, findings highlight the importance of secure attachment to the mother and positive automatic thoughts in combating depressive symptoms; thus ensuring a healthy psychological development for adolescents.